Evaluación del uso de presiones intrabdominales baja, estándar y alta durante la colecistectomía laparoscópica: cambios en la morbimortalidad. - Sayay Tenesaca, Edison Nestor (2024)
This study is centered on the evaluation of low, standard, and high intra-abdominal pressures during laparoscopic cholecystectomy and their direct impact on morbidity and mortality. Our approach is qualitative, utilizing theoretical research methods and drawing from a wide range of bibliographic sources. We conducted a comprehensive literature review, analyzing the results of previous studies and organizing the most relevant data. The study population includes research developed in the last five years and published in reliable scientific databases. During the research, inclusion and exclusion criteria were assessed to determine the studies most relevant for the research development. The final sample consists of 18 open-access scientific publications. The study revealed that low intra-abdominal pressure showed better postoperative pain and analgesic use outcomes. Conversely, it was identified that high intraabdominal pressures are associated with minor postoperative complications such as nausea and vomiting. Our study has identified the pathophysiological changes observed in patients and concluded that low intra-abdominal pressures are the most suitable for laparoscopic cholecystectomy. The discussion of the main results from previous research has underscored the importance of tailoring intra-abdominal pressure to the patient's clinical context. However, our findings also highlight the need for further research in this field to continue improving the morbidity and mortality of patients undergoing laparoscopic surgery.